Comparing microbiotas of foals and their mares’ milk in the first two weeks after birth - Michael J. Mienaltowski; Mitchell Callahan; Ubaldo De La Torre; Elizabeth A. Maga (BMC Veterinary Research, 2024)
Abstract Background The mare-foal relationship is essential for the well-being and growth of a foal. Mare’s milk provides a foal with nutrients, protective immunity, and microbes. Within the first two weeks of life, there is a risk for a foal to suffer from diarrhea, particularly “foal heat diarrhea” which happens at about the time of a mare’s estrus cycle but is more likely due to transitions in the microbiota in the foal’s gastrointestinal (GI) tract. We hypothesized that this GI microbiota transition could be caused by changes in lysozyme and microbial populations in the mare’s milk. To test this hypothesis, fifteen mare-foal pairs were followed in the first 15 days post-foaling. Every other day milk was collected from mares and rectal swabs were collected from foals. Lysozyme activity in the mare’s milk was measured using a fluorescence assay. Microbial DNA was isolated from the milk and swabs and the V4 domain of 16 S rRNA genes were PCR amplified and sequenced using Illumina MiSeq technology. Microbial populations were analyzed using DADA2 and phyloseq within R. Results Mare’s milk lysozyme activity peaked for samples at Day 1 and levels dropped to 72.5% of Day 1 activity by Day 15; however, microbial populations in the mare’s milk did not vary significantly over the two weeks. Furthermore, levels of microbial diversity found in foal rectal swabs were initially similar to microbial diversity seen in mare’s milk; however, over the first fifteen days, diversity increased for the foal rectal swab microbiota and swab microbial populations differed from milk microbes. A transition occurred shifting from microbes from the phylum Proteobacteria early in rectal swabs to those primarily from the phyla Firmicutes and Bacteroidota after the first few days post-foaling. These phyla contained several families and genera of microbes that promote utilization of milk components in healthy gut transition. Microbial abundance levels correlated more with days post-parturition than with lysozyme activity and mare’s milk microbial populations. Conclusions The findings suggest that much of the microbial populations responsible for the transition of the foal’s gut comes from sources outside of mare’s milk species and levels of lysozyme activity.